Fonološki opis govora grada Gerovo (prema zapisu Božidara Finke) - Gostenčnik, Januška (Slavia Centralis, 2020)
In this paper the phonology of the dialect of the town of Gerovo in Gorski kotar in Croatia is presented in the form of a phonological description. The description is based on the material collected by Božidar Finka in 1966 for the Serbo-Croatian dialectological atlas. In some cases the system could not be determined, therefore additions were made with the material gathered by the author in the town of Gerovo. Traditionally, Croatian dialectology classifies the speech of Gerovo as a variety of the Kajkavian dialect group, but the Kajkavian determinative characteristics can not be applied to it. However, Slovene characteristics can be. Therefore, in the description of the speech we take the basic Slovene system as a point of departure.
Keywords: Gorski kotar; goranski dialect; Kajkavian dialect; phonology; prosody